Hydrophilic and antimicrobial core–shell nanoparticles containing guanidine groups for ultrafiltration membrane modification. Issue 44 (9th July 2018) - Gao, Yongqiang; Liang, Lei; Zhao, Song; Qi, Yunlong; Zhang, Wen; Sun, Xuefei; Wang, Zhi; Wang, Jixiao; Song, Baodong
Abstract : Hydrophilic and antimicrobial core–shell nanoparticles containing guanidine groups (SNP@PG) were applied to fabricate membranes with improved water flux and fouling resistance. Abstract : Physical blending is a common technique to improve the water flux and antifouling performance of ultrafiltration (UF) membranes. In the present work, a novel hydrophilic and antimicrobial core–shell nanoparticle was synthesized through the chemical grafting of poly(guanidine-hexamethylenediamine-PEI) (poly(GHPEI)) on the surface of silica nanoparticles (SNP). The synthesized core–shell nanoparticles, poly(GHPEI) functionalized silica nanoparticles (SNP@PG), were incorporated into polyethersulfone (PES) to fabricate hybrid UF membranes by a phase inversion process. The chemical composition, surface and cross section morphologies, hydrophilicity, water flux and protein rejection of the membranes were evaluated by a series of characterizations. Results show that the prepared PES/SNP@PG hybrid membrane exhibits not only improved water flux, which is around 2.6 times that of the pristine PES membrane, but also excellent resistance to organic fouling and biofouling.